Interfacial microstructure and thermal shock resistance of diffusion bonding ODS-W and molybdenum alloy by spark plasma sintering. (September 2022) - Liu, Dong-Guang; Meng, Lin; Ruan, Chong-Fei; Luo, Lai-Ma; Wu, Yu-Cheng
Abstract: In the four temperature ranges of 1300–1600 °C, the diffusion bonding of oxide dispersion enhanced tungsten (ODS-W) and molybdenum hafnium carbon (MHC) alloy prepared by mechanical alloying method was successfully prepared by spark plasma sintering (SPS). In this work, the interface microstructure, mechanical properties and thermal shock resistance of ODS-W/MHC are studied. At above 1500 °C, the W and Mo elements at the ODS-W/MHC interface begin to diffuse, and the diffusion distance can reach 2 μm at 1600 °C. Similarly, the tensile strength of ODS-W/MHC joints is best performed at 1600 °C, with tensile strengths of 425 MPa and 801 MPa at room temperature and 500 °C, respectively. However, as the sintering temperature increased, the hardness of the MHC gradually increased, and ODS-W would recrystallize, resulting in a hardness at the interface between the hardness values of the two substrates. At 1600 °C, the maximum hardness at the sample junction can reach 487 HV. The transient thermal load of the connector during operation is simulated by laser beam and thermal shock experiments are performed on the surface and interface of the ODS-W/MHC connector prepared at different temperatures. Compared with ODS-W, the surface of ODS-W/MHC has no obvious cracks after laser thermal shock, and the cracks generated by the sample interface above 1500 °C have also been greatly improved. It can be seen from CLSM analysis that the height undulation of the surface and interface of ODS-W/MHC is significantly smaller than that of ODS-W, so the ODS-W/MHC prepared at 1600 °C has good thermal shock resistance. Highlights: The diffusion bonding ofODS-W and MHC prepared by mechanical alloying and SPS. At above 1500 °C, the W and Mo elements at the ODS-W/MHC interface began to diffuse, and the diffusion distance reached 2 μm at 1600 °C. The tensile strength of the ODS-W/MHC joints prepared at 1600 °C at room temperature and 500 °C was 425 MPa and 801 MPa.